School Literacy Movement At State Elementary School In Kute Panang District, Central Aceh Regency - Rahmah A.; Alfi Syahrin; Riandi Marisa (Journal Prakarsa Paedagogia, 2024)
The purpose of this study was to describe (1) the implementation of the school literacy movement program at the Kute Panang District Elementary School, and (2) the obstacles faced by the school in implementing the school literacy movement. The research method used in this study is qualitative research. Qualitative research in this case aims to understand social phenomena (students, teachers, principals, committees, and those involved in this study) or human behavior through in-depth interpretation and analysis of non-numerical data. Data collection was obtained from valid and accountable informants, the success of the study depends on the data collection technique itself. So the techniques that will be used in this study are 3 techniques, namely observation, interviews, and documentation. The findings of this study indicate that the components in the implementation of the school literacy movement, namely planning and implementation. This study has the addition of two components in the implementation of the school literacy movement. The addition is in the form of organizing and controlling components. Then, the obstacles faced in the implementation of the school literacy movement can be overcome with comprehensive and sustainable efforts from all related parties. By overcoming these obstacles, it is hoped that the school literacy movement can run effectively and achieve its goals of increasing reading interest and literacy culture in schools.